Role of mother’s education and antenatal counselling on breast feeding practices among women in coastal Karnataka: a community based cross sectional study - K., Chethana; Nelliyanil, Maria; Anil, Manjula; S., Jayaram (International Journal Of Community Medicine And Public Health, 2019)
Background: Breastfeeding has been a universal practice. A number of factors influence the breastfeeding practices of the mothers. This study was conducted to assess the breast-feeding practices and its association with mother’s education and antenatal counselling. Methods: A community based cross sectional study was conducted among 167 mothers with infants who were residing in field practice area of a medical college. A pretested semi-structured validated questionnaire was administered to assess the breast-feeding practices followed. Towards the end of each interview the investigator observed the mothers as they breast fed their children to assess the appropriateness of positioning and attachment. Chi-square test and Fischer’s exact probability test were used to test the associations. Results: 19.8% of the mothers were illiterate. 64.1% had received antenatal counselling on breast feeding. 62.3% initiated breast feeding within one hour. Colostrum was discarded by 6% of the mothers and 28.7% gave pre-lacteal feeds. 72.3%, 86.1% and 77.3% of them practiced appropriate position of feeding, held their children in the appropriate position and had good attachment to the breast, respectively. Mother’s education had a statistically significant association with pre-lacteal feeds administration, exclusive breastfeeding and breast-feeding position. Antenatal breast-feeding counselling had a statistically significant association with appropriate positioning of the child, attachment and practicing burping. Conclusions: Breast feeding practices in the current study was far from satisfactory. Mother’s education and antenatal breast-feeding counselling had a major role in the feeding practices.